PROTOCOL: School Absenteeism Among Children and Young People With Disabilities: A Systematic Review - Lara Stauvermann; Meike Rau; Vivian Meyer; Isabella Sasso; Michael Feldhaus; Karsten Speck (Campbell Systematic Reviews)
ABSTRACT The systematic review set out in this protocol aims to identify factors influencing school absenteeism among children and young people with disabilities. The focus is on individual, family, and school‐related factors that contribute to absenteeism. The analysis will be based on a qualitative synthesis of the extracted data and findings from the included empirical studies. To achieve this, the review will incorporate qualitative, quantitative, and mixed‐methods studies.